Seed coat and variety of peanut inhibits host preference and development of Oryzaephilus mercator. (September 2018) - Astuti, Ludji Pantja; Rizali, Akhmad; Tanzilia, Shanas
Abstract: Oryzaephilus mercator (Fauvel) (Coleoptera: Silvanidae) is a postharvest pest of stored peanuts ( Arachis hypogea L.). Although it is only a secondary pest, this insect causes extensive damage and reduces the quantity and quality of peanut kernels. The objective of this research was to study whether host preference and development of O. mercator differ depending on the variety of peanut and/or on whether the peanut retains its seed coat or is bare. We used three varieties of peanut (Kelinci, Bison and Takar1) separating out each variety into groups with or without a seed coat. In the laboratory, we conducted two separate studies examining host preference and development of O. mercator . Host preference was studied using a preference cage consisting of six chambers for all peanut varieties with and without seed coat and each cage contained 15 mating pairs of O. mercator . The development study was conducted by placing 15 mating pairs of O. mercator into a treatment jar and allowing them to feed on different peanut varieties with and without a seed coat. Results from the host preference study indicated that O. mercator preferred bare kernels of the Kelinci variety over other peanut varieties both as a food source and for oviposition. During the development experiment, we observed that O. mercator experienced faster development time when exposed to bare kernels of all three varieties tested as opposed to those with intact seed coat. Results show that peanuts with a seed coat and variety with high kernel hardness (Bison variety) deters predation and inhibits host preference and development of O. mercator . Highlights: O. mercator preferred bare kernels of the Kelinci variety of peanut. O. mercator experienced faster development time when exposed to bare kernels. Seed coat presence/absence had a significant influence on host preference and on development of O. mercator . Peanuts with a thick seed coat inhibits feeding activity as well as increased mortality of O. mercator adults.